Age and compositional evolution of Sahand volcano in the context of post-collisional magmatism in northwestern Iran: evidence for time-transgressive magmatism away from the collisional suture - Ghalamghash, Jalil; Schmitt, Axel Karl (Lithos, 2019)
Sahand volcano along with the two neighbouring volcanic systems of Saray and Sabalan are three Late Miocene-Quaternary volcanoes that formed in the wake of the collision between the Arabian and Eurasian continental plates along the Neo-Tethyan suture zone in northwestern Iran. Sahand volcano is an isolated, extensive (3707m elevation; >3000km2 area) stratovolcanic complex, which is located ~165km north of the Neo-Tethyan suture zone and was constructed over ~45km thick continental crust. Andesitic to dacitic pyroclastic deposits, ignimbrites, and lava flows form the now strongly eroded Paleo- and Meso-Sahand edifice. Paleo-Sahand rocks are mostly restricted to the central part the edifice, where they underlie Meso-Sahand deposits. By contrast, Neo-Sahand volcanic rocks intruded older volcanic successions within and outside a largely eroded caldera margin, which likely formed during the Meso-Sahand stage. Neo-Sahand units comprise several basaltic andesitic to rhyolitic domes in the center of the complex as well as small parasitic cones along with subvolcanic dikes. High spatial resolution and sensitivity U-Pb geochronology using secondary ionization mass spectrometry (SIMS) define the formation of Paleo-, Meso-, and Neo-Sahand to ca. 8 to 3Ma, ca. 1Ma, and ca. 600 to <173ka, respectively, with dating mostly focusing on Neo-Sahand. Antecrystic zircon crystals in Sahand volcanic deposits also indicate that post-collisional magmatism initiated locally at about the same time or slightly earlier than at Saray volcano to the west of Sahand. The initiation of volcanic activity subsequently migrated to the northeast over a distance of ~300km away from the Neo-Tethyan suture, where activity started at Sabalan volcano at ca. 4.5 to 2.9Ma. This time corresponds to a magmatic lull of Sahand before the Meso-Sahand eruptive activity resumed at ca. 1Ma. Subsequently, Neo-Sahand and Neo-Sabalan erupted synchronously throughout the middle and possibly into the late Pleistocene. Paleo- and Neo-Sahand volcanic rocks are characterized by enrichments of large-ion lithophile (LILE) and light rare earth elements (LREE) relative to high-field strength and heavy rare earth elements (HREE), respectively, and prominent negative Ti, Nb, and Ta anomalies relative to primitive mantle compositions. The least evolved magmas at Sahand have formed by 1-5% partial melting of garnet- and spinel-peridotite and were subsequently overprinted through assimilation - fractional crystallization (AFC) processes acting in the continental crust. Although Sahand and Sabalan volcanic rocks share many geochemical characteristics indicative of a continental subduction setting, Sahand is less potassic and less enriched in incompatible trace elements compared to Sabalan. Another difference is that Sahand primitive magmas were formed by smaller degrees of partial melting in the mantle than is the case for Sabalan. Both effects likely result from variable distances from the suture zone and crustal thickening away from the suture towards the northeast. Overall, the apparent age progression and geochemical variation of the post-collisional volcanism, lack of asthenospheric mantle components, and the subduction-affinity of Sahand and Sabalan volcanic rocks supports a scenario where mantle melting was triggered by slab roll back and break-off shortly after continental collision, followed by migration of the slab edge towards the northeast at plate-like velocities.
Gesehen am 01.10.2019